Downregulation of Src-family tyrosine kinases by Srcasm and c-Cbl: A comparative analysis - Vivian Lee (Wolters Kluwer Medknow Publications, 2021)
AIM: Elevated Src-Family tyrosine kinase (SFK) activity drives carcinogenesis in vivo and elevated SFK activity is found ubiquitously in human cancers. Although human squamous cell carcinomas (SCCs) demonstrate increased SFK activity, in silico analysis of SCCs demonstrates that only 0.4% of lesions contain mutations that could potentially increase SFK activity; similarly, a low frequency of activating SFK mutations is found in other major cancers. These findings indicate that SFK activation in cancers likely is not due to activating mutations but alternative mechanisms. To evaluate potential alternative mechanisms, we evaluated the selectivity of c-Cbl and Srcasm in downregulating native and activated mutant forms of SFKs.MATERIALS AND METHODS: We co-transfected native and activated forms of Src and Fyn with c-Cbl and Srcasm into HaCaT cells and monitored the ability of Srcasm and c-Cbl to downregulate native and activated forms of SFKs by Western blotting. The mechanism of downregulation was probed using mutant forms of Srcasm and c-Cbl and using proteosomal and lysosomal inhibition.RESULTS: The data indicate that Srcasm downregulates native Fyn and Src more effectively than c-Cbl, whereas c-Cbl preferentially downregulates activated SFK mutants, including Fyn Y528F, more effectively than Srcasm. Srcasm downregulates SFKs through a lysosomal-dependent mechanism while c-Cbl utilizes a proteosomal-dependent mechanism.CONCLUSION: Given the rarity of activating SFK mutations in human cancer, these data indicate that decreasing Srcasm level/function may represent a mechanism for increasing SFK activity in SCC and other human tumors.